Cell Division in Escherichia coli: Analysis of Double Mutants for Filamentation and Abnormal Septation of Deoxyribonucleic Acid-Less Cells - Zusman, David R. (1974)
The link between chromosome termination, initiation of cell division, and choice of division sites was studied in Escherichia coli by preparing double mutants. Hybrid mutants containing div52-ts, a cell division initiation mutation, and min, mutations which affect the choice of division sites resulting in the septation of minicells, were characterized. The mutants produced minicells and normal cells coordinately under all conditions studied, although the fraction of minicells is half that of the parental minicell strain. The mutant gradually stopped dividing at both the median and minicell septation sites when transferred from 30 to 41 C in rich medium. A synchronous cell division of filaments was induced 15 min after addition of chloramphenicol to the medium, even at 41 C. Divisions were observed at both normal and minicell sites. These results indicate that div52-ts and min functions share a common step in a cell division pathway. A double mutant containing div52-ts and div27-ts, a dnaB mutant which divides in the absence of DNA synthesis, was characterized. The mutant continues to divide after a shift to the high temperature, although at a reduced rate. The behavior of this hybrid mutant suggests a hypothesis that the chromosome termination signal and div52-ts division initiation signal act on a single membrane site which is altered in div27-ts strains.